Evaluating the Diagnostic Proficiency Among a Sample of Final Stage Dental Students in Some Orthodontic Cases: A Comprehensive Analysis of Clinical Competence - Noor Nourie Abbass; Zainab Mousa Kadhom; Wurood Khairallah Al-Lehaibi; Mohammed Nahidh (Dentistry Journal)
Background/Objectives: This study evaluates the diagnostic and referral skills of final-year dental students at Al-Iraqia University using a questionnaire based on malocclusion cases ranging from mild to severe. Methods: The questionnaire, featuring photos and radiographs of five selected treated cases from two textbooks, was answered by 165 students who were asked to assess each case and determine whether orthodontic or surgical treatment was necessary, as well as to identify factors contributing to an unesthetic profile, such as irregular teeth. Frequency distribution and the Chi-square test were used for statistical analysis. Results: The results indicated good overall clinical competence. The unesthetic profile and irregular teeth were the main reasons for referring both Class II and III cases for surgery, with mandibular retrusion being the most common factor in aesthetic concerns. Maxillary protrusion was less frequently selected as a key factor in Class II malocclusion cases. Conclusions: The findings suggest that students demonstrated a high level of diagnostic accuracy in identifying treatment needs for various malocclusion cases.